Synthesis and Applications of \(α\)-Oxodithioesters - Swaroop, Toreshettahally R; Suresh, Rajaghatta N; Umashankara, Muddegowda; Rangappa, Kanchugarakoppal S (Chemistry and Biochemistry: Research Progress Vol. 4, 2025)
In this chapter, we present the synthesis of \(α\)-oxodithioesters and their applications for the synthesis of heterocyclic compounds. At first, we report the synthesis of 2-(methylthio)-3-(het) arylquinoxalines by the cyclocondensation of o-phenylenediamines with \(α\)-oxodithioesters catalyzed by p-toluenesulfonic acid (p-TSA) in toluene at 80°C. 2-Acylbenzoxazoles are formed when o-aminophenols react with \(α\)-oxodithioesters under similar reaction conditions. Besides, 4-methylthio-5-acylthiazoles are obtained when \(α\)-oxodithioesters are reacted with tosylmethyl isocyanide in aqueous alcoholic potassium hydroxide media. Similarly, a reaction between ethyl isocyanoacetate and \(α\)-oxodithioesters in ethanol in the presence of DBU-furnished ethyl 5-acylthiazole carboxylates. The p-TSA catalyzed cyclocondensation of anthranilamide with \(α\)-oxodithioesters in DMF at 120°C produced 2-acylquinazolin-4(3H)-ones. Finally, a reaction between \(α\)-oxodithioesters and anthranilamide in refluxing acetic acid formed 2-acyl-4H-benzo[d][1,3] thiazin-4-ones.